Kajian Perbandingan Asas Nasionalitas Hukum Agraria dalam Konteks Internasional - Prithresia, Bianca (UNES Law Review, 2023)
One key aspect of agrarian law is the principle of nationality, questioning who has the right to own and manage land and its natural resources within a jurisdiction. This research employs a comparative legal approach to identify similarities and differences in the nationality principles of agrarian law between Indonesia and several other countries. The countries chosen as examples in this study are Singapore, the Philippines, and Saudi Arabia. The research findings indicate that the nationality principle in agrarian law in Indonesia is based on principles involving restrictions on land ownership by foreigners and prioritizing Indonesian citizens. On the other hand, other countries have different approaches to the nationality of their agrarian laws; some may adopt more liberal systems, while others may enforce stricter rules regarding land ownership by foreign nationals. This comparison provides valuable insights into how the nationality principle in agrarian law can impact economic development, foreign investment, and the protection of the rights of local communities. Furthermore, the results of this research also have significant implications in the context of globalization and cross-border investments. This study can serve as a foundation for policymakers to consider agrarian law reforms to enhance investment attractiveness and safeguard the rights of communities.